Presence of political discourses regarding immigration within the government programs for the elections in Costa Rica, 2017-2018 (Revista Rupturas, 2019)
The present paper systematizes and provides an analysis of the political discourses regarding the topics of immigration and immigrants, presented in the government proposals of the national political parties participating during the presidential and legislative elections, in Costa Rica, for the period 2017-2018.The proposal focuses in the discourses, considering them as a continuum between re-active and pro-active discourses facing the immigration phenomenon, situation which evidences the conception of the political parties as fundamental actors in the formulation of public policies that will affect the immigrant population.
Keywords: inmigration; elections; politics; migration